Bi-based composite catalyst based on ZIF-67 as well as preparation method and application of Bi-based composite catalyst

Through the preparation method of the Bi-based composite catalyst based on ZIF-67, the problems of insufficient activity, selectivity and stability of Bi-based catalysts in the prior art are solved, and the effect of efficient electrocatalytic reduction of CO2 to make formic acid is achieved.

CN119900050APending Publication Date: 2025-04-29HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510120093.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

It is difficult to develop a Bi-based catalyst with high activity, high selectivity and high stability for electrocatalytic reduction of CO2 to formic acid.

Method used

ZIF-67 is used to react 2-methylimidazole and cobalt nitrate to form ZIF-67 by reacting 2-methylimidazole and cobalt nitrate, then mixing with methanol and acid solution to form ZIF-67K, then reacting with bismuth nitrate to form Bi-ZIF-67K, and exposing Bi's active sites through calcination, thereby enhancing the catalytic activity of the catalyst.

Benefits of technology

The high stability and long life of the catalyst are achieved, while the catalytic activity and Faraday efficiency are improved, and it is highly selectively used in electrocatalytic reduction of CO2 to make formic acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900050A_ABST
    Figure CN119900050A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalytic reduction of CO2, and provides a Bi-based composite catalyst based on ZIF-67 as well as a preparation method and application of the Bi-based composite catalyst. The preparation method comprises the following steps: mixing 2-methylimidazole and methanol to obtain a methanol solution of 2-methylimidazole, and mixing cobalt nitrate and methanol to obtain a methanol solution of cobalt nitrate; the preparation method comprises the following steps: reacting a methanol solution of 2-methylimidazole with a methanol solution of cobalt nitrate to obtain ZIF-67; the preparation method comprises the following steps: mixing ZIF-67, methanol and an acid solution to obtain ZIF-67K; the preparation method comprises the following steps: reacting ZIF-67K, bismuth nitrate and water to obtain Bi-ZIF-67K; and the Bi-ZIF-67K is subjected to calcination. The ZIF-67 is used for providing a framework, so that the stability of the catalyst is improved, and the service life is prolonged; the ZIF-67 provides metal contact sites after being etched, active sites of Bi are exposed through calcination, and the activity, Faraday efficiency and selectivity of the catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to electrocatalytic reduction of CO 2 The technical field relates to a Bi-based composite catalyst based on ZIF-67 and a preparation method and application thereof. Background Art

[0002] With the continuous development of science and technology, people's demand for energy has increased dramatically, and the resulting excessive consumption of fossil fuels has caused a serious energy crisis and greenhouse effect. 2 The main direction of resource utilization is to transform it into high value-added products. 2 The conversion methods include thermal catalysis, photocatalysis, electrocatalysis and biocatalysis. Among them, electrocatalysis has the advantages of mild reaction conditions, operation at room temperature and pressure, and rich and diverse conversion products.

[0003] In many electrocatalytic reduction of CO 2 Among the products, formic acid (HCOOH) has the characteristics of small number of transferred electrons and simple reaction path, and is widely used in commercial synthetic industry (pharmaceuticals, rubber, etc.) and fuel cells. Formic acid is a hydrogen storage medium with great development space and application prospects. The hydrogen mass fraction is 4.4% and the density can reach 1.22g / cm 3 , the volumetric hydrogen storage capacity reaches 53gH 2 / L, which is equivalent to an energy density of 1.77kW·h / L, exceeding the 70MPa hydrogen pressure tank. At the same time, formic acid can be used as a conversion intermediate for a variety of functional groups. For example, formic acid can be used as a hydrogen source for the catalytic reduction of specific functional groups: hydrogenation of unsaturated groups, hydrogenation of carbonyl compounds to alcohols, hydrogenation of imines or nitro groups to amines, hydrogenation of alkynes to alkenes, and hydrogenation of alkenes to alkanes. 2 The catalysts for making formic acid mainly include Sn, Bi, In, Pb, Hg, Cd, TI, etc. Since Pb, Hg, Cd, and TI are highly toxic and harmful to the environment, and the cost of In is relatively high, the most ideal catalyst is Bi.

[0004] Therefore, the electrocatalytic reduction of CO 2 Bi-based catalysts with high activity, high selectivity and high stability in the production of formic acid have broad application prospects. Summary of the invention

[0005] The purpose of the present invention is to provide a Bi-based composite catalyst based on ZIF-67 and a preparation method and application thereof in view of the deficiencies in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a Bi-based composite catalyst based on ZIF-67, comprising the following steps:

[0008] 1) mixing 2-methylimidazole and methanol to obtain a methanol solution of 2-methylimidazole;

[0009] mixing cobalt nitrate and methanol to obtain a methanol solution of cobalt nitrate;

[0010] 2) reacting a methanol solution of 2-methylimidazole and a methanol solution of cobalt nitrate to obtain ZIF-67;

[0011] 3) mixing ZIF-67, methanol and acid solution to obtain ZIF-67K;

[0012] 4) reacting ZIF-67K, bismuth nitrate and water to obtain Bi-ZIF-67K;

[0013] 5) calcining Bi-ZIF-67K to obtain a Bi-based composite catalyst based on ZIF-67.

[0014] Preferably, the concentration of 2-methylimidazole in the methanol solution of 2-methylimidazole in step 1) is 0.1-0.3 mol / L, the concentration of cobalt nitrate in the methanol solution of cobalt nitrate is 0.05-0.2 mol / L, and the molar ratio of 2-methylimidazole to cobalt nitrate is 3-5:1.

[0015] Preferably, the reaction temperature in step 2) is 20-30° C., the reaction time is 1-3 h, and stirring is performed during the reaction at a speed of 500-700 r / min.

[0016] Preferably, the acid solution in step 3) is a phytic acid solution, and the mass fraction of the phytic acid solution is 1 to 8%;

[0017] The mass volume ratio of the ZIF-67, methanol and acid solution is 0.5 g: 180-200 mL: 370-400 mL.

[0018] Preferably, in step 3), the mixing temperature is 20-30° C., the mixing time is 0.5-3 h, and stirring is performed during the mixing process at a stirring speed of 500-700 r / min.

[0019] Preferably, in step 4), the mass volume ratio of ZIF-67K to water is 100 mg: 10-20 mL, and the mass molar ratio of ZIF-67K to bismuth nitrate is 100 mg: 1.5-3 mmol.

[0020] Preferably, the reaction temperature in step 4) is 20-30° C., the reaction time is 2-4 h, and stirring is performed during the reaction at a speed of 450-650 r / min.

[0021] Preferably, the calcination in step 5) is carried out under an argon atmosphere, and the calcination includes a primary calcination and a secondary calcination;

[0022] The primary calcination temperature is 250-350°C, the primary calcination time is 10-30 min, and the heating rate to the primary calcination temperature is 4-6°C / min;

[0023] The temperature of the secondary calcination is 750-850° C., the time of the secondary calcination is 1-3 hours, and the heating rate to the secondary calcination temperature is 4-6° C. / min.

[0024] The present invention also provides a Bi-based composite catalyst based on ZIF-67 prepared by the preparation method.

[0025] The present invention also provides the Bi-based composite catalyst based on ZIF-67 in the electrocatalytic reduction of CO 2 Application in the production of formic acid.

[0026] The beneficial effects of the present invention include the following:

[0027] 1) The present invention uses ZIF-67 to provide a framework, and the ZIF-67 skeleton structure improves the stability of the catalyst and prolongs the service life of the catalyst; ZIF-67 provides metal contact sites after phytic acid etching, introduces Bi, and exposes the active sites of Bi through calcination, thereby improving the catalytic activity of the catalyst; at the same time, ZIF-67 provides phosphorus elements, thereby improving the Faraday efficiency and catalytic activity of the catalyst.

[0028] 2) The Bi-based composite catalyst prepared by the present invention has abundant Bi active sites and good electrical conductivity and magnetism, and is effective in the electrocatalytic reduction of CO 2 It has high selectivity in the production of formic acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The X-ray diffraction pattern of ZIF-67 prepared in Example 1;

[0030] Figure 2 X-ray diffraction patterns of the Bi-based composite catalyst and bismuth phosphate prepared in Example 1, Comparative Example 1 and Comparative Example 2;

[0031] Figure 3 This is a diagram of the electrochemical performance test device;

[0032] Figure 4The hydrophobic carbon paper (supported catalyst) of Application Example 1 was subjected to CO 2 , linear sweep voltammetry curves in Ar atmosphere;

[0033] Figure 5 For Application Example 1, the hydrophobic carbon paper (loaded catalyst) of Comparative Example 1 was used in the electrocatalytic reduction of CO 2 Faradaic efficiency of formic acid production;

[0034] Figure 6 The hydrophobic carbon paper (loaded with catalyst) of Application Example 1 was used for electrocatalytic reduction of CO at 0.8 V vs. RHE. 2 Faradaic efficiency and current density for the production of formic acid. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a Bi-based composite catalyst based on ZIF-67, comprising the following steps:

[0036] 1) mixing 2-methylimidazole and methanol to obtain a methanol solution of 2-methylimidazole;

[0037] mixing cobalt nitrate and methanol to obtain a methanol solution of cobalt nitrate;

[0038] 2) reacting a methanol solution of 2-methylimidazole and a methanol solution of cobalt nitrate to obtain ZIF-67;

[0039] 3) mixing ZIF-67, methanol and acid solution to obtain ZIF-67K;

[0040] 4) reacting ZIF-67K, bismuth nitrate and water to obtain Bi-ZIF-67K;

[0041] 5) calcining Bi-ZIF-67K to obtain a Bi-based composite catalyst based on ZIF-67.

[0042] In the present invention, the concentration of 2-methylimidazole in the methanol solution of 2-methylimidazole in step 1) is preferably 0.1-0.3 mol / L, more preferably 0.15-0.25 mol / L, more preferably 0.2 mol / L; the concentration of cobalt nitrate in the methanol solution of cobalt nitrate is preferably 0.05-0.2 mol / L, more preferably 0.08-0.15 mol / L, more preferably 0.1 mol / L; the molar ratio of 2-methylimidazole to cobalt nitrate is preferably 3-5:1, more preferably 3.5-4.5:1, more preferably 4:1.

[0043] In the present invention, the temperature of the reaction in step 2) is preferably 20-30°C, more preferably 22-28°C, and more preferably 25°C; the reaction time is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h; stirring is preferably performed during the reaction, and the stirring speed is preferably 500-700r / min, more preferably 550-650r / min, and more preferably 600r / min.

[0044] In the present invention, after the reaction in step 2) is completed, centrifugation, washing and drying are preferably performed in sequence to obtain ZIF-67; the centrifugal speed is preferably 8000-10000 r / min, more preferably 9000 r / min, and the centrifugal time is preferably 3-8 min, more preferably 5 min; the reagent used for washing is preferably methanol; the drying temperature is preferably 50-70°C, more preferably 60°C, and the drying time is preferably 10-14 h, more preferably 12 h.

[0045] In the present invention, the acid solution in step 3) is preferably a phytic acid solution, and the mass fraction of the phytic acid solution is preferably 1-8%, more preferably 3-6%, and more preferably 5%;

[0046] The mass volume ratio of the ZIF-67, methanol and acid solution is preferably 0.5 g: 180-200 mL: 370-400 mL, more preferably 0.5 g: 185-195 mL: 380-390 mL, and more preferably 0.5 g: 192 mL: 384 mL.

[0047] In the present invention, the mixing temperature in step 3) is preferably 20-30°C, more preferably 22-28°C, and more preferably 25°C; the mixing time is preferably 0.5-3h, more preferably 1-2h, and more preferably 1.5h; stirring is preferably performed during the mixing process, and the stirring speed is preferably 500-700r / min, more preferably 550-650r / min, and more preferably 600r / min.

[0048] In the present invention, after the mixing in step 3) is completed, centrifugation, washing and drying are preferably performed in sequence to obtain ZIF-67K; the centrifugal speed is preferably 8000-10000 r / min, more preferably 9000 r / min, and the centrifugal time is preferably 3-8 min, more preferably 5 min; the reagent used for washing is preferably water; the drying temperature is preferably 50-70°C, more preferably 60°C, and the drying time is preferably 10-14 h, more preferably 12 h.

[0049] In the present invention, the mass volume ratio of ZIF-67K and water in step 4) is preferably 100 mg: 10-20 mL, more preferably 100 mg: 12-18 mL, and more preferably 100 mg: 15 mL; the mass molar ratio of ZIF-67K and bismuth nitrate is preferably 100 mg: 1.5-3 mmol, and more preferably 100 mg: 2-2.5 mmol.

[0050] In the present invention, the temperature of the reaction in step 4) is preferably 20-30°C, more preferably 22-28°C, and more preferably 25°C; the reaction time is preferably 2-4h, more preferably 2.5-3.5h, and more preferably 3h; stirring is preferably performed during the reaction, and the stirring speed is preferably 450-650r / min, more preferably 500-600r / min, and more preferably 550r / min.

[0051] In the present invention, after the reaction in step 4) is completed, centrifugation, washing and drying are preferably performed in sequence to obtain Bi-ZIF-67K; the centrifugal speed is preferably 8000-10000 r / min, more preferably 9000 r / min, and the centrifugal time is preferably 3-8 min, more preferably 5 min; the reagent used for washing is preferably water; the drying temperature is preferably 50-70°C, more preferably 60°C, and the drying time is preferably 10-14 h, more preferably 12 h.

[0052] In the present invention, the calcination in step 5) is preferably carried out under an argon atmosphere, and the calcination preferably includes a primary calcination and a secondary calcination;

[0053] The primary calcination temperature is preferably 250-350°C, more preferably 280-320°C, and more preferably 300°C; the primary calcination time is preferably 10-30 min, more preferably 15-25 min, and more preferably 20 min; the heating rate to the primary calcination temperature is preferably 4-6°C / min, more preferably 4.5-5.5°C / min, and more preferably 5°C / min;

[0054] The temperature of the secondary calcination is preferably 750-850°C, more preferably 780-820°C, and more preferably 800°C; the time of the secondary calcination is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h; the heating rate to the secondary calcination temperature is preferably 4-6°C / min, more preferably 4.5-5.5°C / min, and more preferably 5°C / min.

[0055] In the present invention, after the calcination in step 5) is completed, it is preferably cooled first and then naturally cooled. The cooling rate is preferably 2-3°C / min, more preferably 2.5°C / min, and the temperature is preferably cooled to 180-220°C, more preferably 200°C.

[0056] The present invention also provides a Bi-based composite catalyst based on ZIF-67 prepared by the preparation method.

[0057] The present invention also provides the Bi-based composite catalyst based on ZIF-67 in the electrocatalytic reduction of CO 2 Application in the production of formic acid.

[0058] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0059] Example 1

[0060] 384 mL of 2-methylimidazole methanol solution (the concentration of 2-methylimidazole in the 2-methylimidazole methanol solution is 0.2 mol / L) and 192 mL of cobalt nitrate methanol solution (the concentration of cobalt nitrate in the cobalt nitrate methanol solution is 0.1 mol / L) were mixed, and stirred at 25°C at a speed of 600 r / min for 2 hours to obtain a mixed solution. The mixed solution was centrifuged at a speed of 9000 r / min for 5 minutes, and then the centrifuged product was washed with methanol until the washing solution was colorless, and then dried at 60°C for 12 hours to obtain ZIF-67.

[0061] 0.5 g ZIF-67, 192 mL methanol and 384 mL phytic acid aqueous solution (mass fraction of phytic acid aqueous solution is 5%) were mixed and stirred at 600 r / min for 1 h at 25°C to obtain a suspension. The suspension was centrifuged at 9000 r / min for 5 min, and then the centrifuged product was washed with deionized water until the washing liquid was colorless, and then dried at 60°C for 12 h to obtain ZIF-67K.

[0062] 100 mg of ZIF-67K was placed in 15 mL of deionized water and stirred at 550 r / min for 10 min to uniformly disperse ZIF-67K to obtain an aqueous solution of ZIF-67K. 2.5 mmol of bismuth nitrate pentahydrate was added to the aqueous solution of ZIF-67K, and the mixture was stirred at 550 r / min for 3 h at 25 ° C to obtain a suspension. The suspension was centrifuged at 9000 r / min for 5 min, and the centrifuged product was washed with deionized water until the washing solution was colorless, and then dried at 60 ° C for 12 h to obtain Bi-ZIF-67K.

[0063] Bi-ZIF-67K was placed in a tubular furnace, the air in the tubular furnace was evacuated, and then argon was introduced at a flow rate of 0.2L / min. The tubular furnace was heated to 300°C at a rate of 5°C / min and kept at 300°C for 20min. Then the tubular furnace was further heated to 800°C at a rate of 5°C / min, and kept at 800°C for 2h for calcination. After the calcination, the tubular furnace was cooled to 200°C at a rate of 2.5°C / min, and then the nitrogen was stopped and the tubular furnace was naturally cooled to room temperature to obtain a Bi-based composite catalyst based on ZIF-67.

[0064] The Bi-based composite catalyst based on ZIF-67 prepared in this example is marked as CoBi-2.5.

[0065] Figure 1 The X-ray diffraction pattern of ZIF-67 prepared in Example 1. Figure 1 It can be seen that the crystal form of ZIF-67 is good.

[0066] Example 2

[0067] 384 mL of 2-methylimidazole methanol solution (the concentration of 2-methylimidazole in the 2-methylimidazole methanol solution is 0.3 mol / L) and 192 mL of cobalt nitrate methanol solution (the concentration of cobalt nitrate in the cobalt nitrate methanol solution is 0.2 mol / L) were mixed, and stirred at 700 r / min at 30°C for 1 h to obtain a mixed solution. The mixed solution was centrifuged at 8000 r / min for 8 min, and the centrifuged product was washed with methanol until the washing solution was colorless, and then dried at 50°C for 14 h to obtain ZIF-67.

[0068] 0.5 g ZIF-67, 180 mL methanol and 370 mL phytic acid aqueous solution (mass fraction of phytic acid aqueous solution is 1%) were mixed and stirred at 500 r / min for 3 h at 20°C to obtain a suspension. The suspension was centrifuged at 8000 r / min for 8 min, and then the centrifuged product was washed with deionized water until the washing liquid was colorless, and then dried at 50°C for 14 h to obtain ZIF-67K.

[0069] 100 mg of ZIF-67K was placed in 10 mL of deionized water and stirred at 650 r / min for 10 min to uniformly disperse ZIF-67K to obtain an aqueous solution of ZIF-67K. 2 mmol of bismuth nitrate pentahydrate was added to the aqueous solution of ZIF-67K, and the mixture was stirred at 650 r / min for 2 h at 30 ° C to obtain a suspension. The suspension was centrifuged at 8000 r / min for 8 min, and the centrifuged product was washed with deionized water until the washing solution was colorless, and then dried at 50 ° C for 14 h to obtain Bi-ZIF-67K.

[0070] Bi-ZIF-67K was placed in a tubular furnace, the air in the tubular furnace was evacuated, and then argon was introduced at a flow rate of 0.2L / min. The tubular furnace was heated to 250°C at a rate of 6°C / min and kept at 250°C for 30min. Then the tubular furnace was further heated to 850°C at a rate of 4°C / min, and kept at 850°C for 1h for calcination. After the calcination, the tubular furnace was cooled to 220°C at a rate of 3°C / min, and then the nitrogen was stopped and the tubular furnace was naturally cooled to room temperature to obtain a Bi-based composite catalyst based on ZIF-67.

[0071] Example 3

[0072] 384 mL of 2-methylimidazole methanol solution (the concentration of 2-methylimidazole in the methanol solution of 2-methylimidazole is 0.1 mol / L) and 153.6 mL of cobalt nitrate methanol solution (the concentration of cobalt nitrate in the methanol solution of cobalt nitrate is 0.05 mol / L) were mixed, and stirred at 20°C at a speed of 500 r / min for 3 hours to obtain a mixed solution. The mixed solution was centrifuged at a speed of 10000 r / min for 3 minutes, and then the centrifuged product was washed with methanol until the washing solution was colorless, and then dried at 70°C for 10 hours to obtain ZIF-67.

[0073] 0.5 g ZIF-67, 200 mL methanol and 400 mL phytic acid aqueous solution (mass fraction of phytic acid aqueous solution is 8%) were mixed and stirred at 700 r / min for 0.5 h at 30°C to obtain a suspension. The suspension was centrifuged at 10000 r / min for 3 min, and then the centrifuged product was washed with deionized water until the washing liquid was colorless, and then dried at 70°C for 10 h to obtain ZIF-67K.

[0074] 100 mg of ZIF-67K was placed in 20 mL of deionized water and stirred at 450 r / min for 10 min to disperse ZIF-67K evenly to obtain an aqueous solution of ZIF-67K. 3 mmol of bismuth nitrate pentahydrate was added to the aqueous solution of ZIF-67K, and the mixture was stirred at 450 r / min for 4 h at 20 ° C to obtain a suspension. The suspension was centrifuged at 10000 r / min for 3 min, and then the centrifuged product was washed with deionized water until the washing solution was colorless, and then dried at 70 ° C for 10 h to obtain Bi-ZIF-67K.

[0075] Bi-ZIF-67K was placed in a tubular furnace, the air in the tubular furnace was evacuated, and then argon was introduced at a flow rate of 0.2L / min. The tubular furnace was heated to 350°C at a rate of 4°C / min and kept at 350°C for 10min. Then the tubular furnace was further heated to 750°C at a rate of 6°C / min, and kept at 750°C for 3h for calcination. After the calcination, the tubular furnace was cooled to 180°C at a rate of 2°C / min, and then the nitrogen was stopped and the tubular furnace was naturally cooled to room temperature to obtain a Bi-based composite catalyst based on ZIF-67.

[0076] Comparative Example 1

[0077] The bismuth nitrate pentahydrate in Example 1 was modified to 0.5 mmol, and the rest was the same as in Example 1.

[0078] The Bi-based composite catalyst prepared in this comparative example is marked as CoBi-0.5.

[0079] Comparative Example 2

[0080] The bismuth nitrate pentahydrate in Example 1 was modified to 1 mmol, and the rest was the same as Example 1.

[0081] The Bi-based composite catalyst prepared in this comparative example is marked as CoBi-1.

[0082] Figure 2 The X-ray diffraction patterns of the Bi-based composite catalyst and bismuth phosphate prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 2 It can be seen that the Bi-based composite catalyst based on ZIF-67 prepared in Example 1 has good crystallinity, the Bi-based composite catalyst of Comparative Example 1 has disordered peaks and poor crystal form, and the Bi-based composite catalyst of Comparative Example 2 has poor crystallinity.

[0083] Application Example 1

[0084] 10 mg of Bi-based composite catalyst CoBi-2.5, 50 μL of dispersant Nafion D520 solution, 475 μL of isopropanol and 475 μL of deionized water were mixed and ultrasonicated at 40 kHz for 1 h to obtain catalytic ink. The catalytic ink was dropped into an area of ​​1.5 cm using a pipette. 2 The hydrophobic carbon paper was evenly coated to obtain a hydrophobic carbon paper (loaded catalyst), wherein the catalyst loading was 1 mg / cm 2 .

[0085] Application Comparative Example 1

[0086] The Bi-based composite catalyst in Application Example 1 was modified to Ce 2 Bi@C, other aspects are the same as those in Application Example 1.

[0087] The electrochemical performance test was carried out on the hydrophobic carbon paper (loaded with catalyst) corresponding to Example 1 and Comparative Example 1. Figure 3 This is a diagram of the electrochemical performance test device. Figure 3 The test device was assembled and the hydrophobic carbon paper (loaded with catalyst) was tested in CO by linear sweep voltammetry using a CHI760E electrochemical workstation from Shanghai Chenhua Instrument Co., Ltd. 2 , current density in Ar atmosphere, and electrocatalytic reduction of CO by hydrophobic carbon paper (supported catalyst) 2 Faradaic efficiency for the production of formic acid.

[0088] Figure 4 The hydrophobic carbon paper (supported catalyst) of Application Example 1 was subjected to CO 2 Linear sweep voltammetry curves of Ar atmosphere. Figure 4 It can be seen that the hydrophobic carbon paper loaded with Bi-based composite catalyst CoBi-2.5 in Application Example 1 has a 2 The current density of linear sweep voltammetry in the atmosphere is significantly higher than that in the Ar atmosphere. This result shows that the Bi-based composite catalyst based on ZIF-67 of the present invention is effective for the electrocatalytic reduction of CO 2 Has strong activity.

[0089] Figure 5 For Application Example 1, the hydrophobic carbon paper (loaded catalyst) of Comparative Example 1 was used in the electrocatalytic reduction of CO 2 Faradaic efficiency of formic acid production. Figure 5 It can be seen that as the voltage increases, the hydrophobic carbon paper (loaded catalyst) of Application Example 1 has a higher electrocatalytic reduction rate of CO 2 The Faraday efficiency in the production of formic acid shows a trend of first increasing and then decreasing; the hydrophobic carbon paper (loaded with catalyst) of Application Example 1 electrocatalytically reduces CO at 0.8 V vs. RHE 2The Faraday efficiency of formic acid production reached 81%. The test results showed that the hydrophobic carbon paper (loaded with catalyst) of Comparative Example 1 electrocatalyzed the reduction of CO at 0.8 V vs. RHE. 2 The Faraday efficiency of formic acid production only reached 78%. During the test, the gaseous products and liquid products were analyzed for their components. When the hydrophobic carbon paper (loaded catalyst) of Application Example 1 was used, the gaseous products were only hydrogen, and the liquid products were only formic acid; when the hydrophobic carbon paper (loaded catalyst) of Comparative Example 1 was used, the gaseous products were hydrogen and carbon monoxide, and the liquid product was formic acid. The results show that the Bi-based composite catalyst based on ZIF-67 of the present invention is effective for the electrocatalytic reduction of CO 2 The production of formic acid has strong selectivity.

[0090] Figure 6 The hydrophobic carbon paper (loaded with catalyst) of Application Example 1 was used for electrocatalytic reduction of CO at 0.8 V vs. RHE. 2 Faradaic efficiency and current density for the production of formic acid. Figure 6 It can be seen that the hydrophobic carbon paper (supported catalyst) of Application Example 1 can still maintain excellent Faradaic efficiency after 24 hours of use. This result shows that the Bi-based composite catalyst based on ZIF-67 of the present invention has excellent stability.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Bi-based composite catalyst based on ZIF-67, characterized in that: The following steps are included: 1) mixing 2-methylimidazole and methanol to obtain a methanol solution of 2-methylimidazole; mixing cobalt nitrate and methanol to obtain a methanol solution of cobalt nitrate; 2) reacting a methanol solution of 2-methylimidazole and a methanol solution of cobalt nitrate to obtain ZIF-67; 3) mixing ZIF-67, methanol and acid solution to obtain ZIF-67K; 4) reacting ZIF-67K, bismuth nitrate and water to obtain Bi-ZIF-67K; 5) calcining Bi-ZIF-67K to obtain a Bi-based composite catalyst based on ZIF-67.

2. The preparation method according to claim 1, characterized in that: Step 1) The concentration of 2-methylimidazole in the methanol solution of 2-methylimidazole is 0.1-0.3 mol / L, the concentration of cobalt nitrate in the methanol solution of cobalt nitrate is 0.05-0.2 mol / L, and the molar ratio of 2-methylimidazole to cobalt nitrate is 3-5:

1.

3. The preparation method according to claim 1 or 2, characterized in that: Step 2) The reaction temperature is 20-30° C., the reaction time is 1-3 hours, and stirring is performed during the reaction at a speed of 500-700 r / min.

4. The preparation method according to claim 3, characterized in that: Step 3) the acid solution is a phytic acid solution, and the mass fraction of the phytic acid solution is 1 to 8%; The mass volume ratio of the ZIF-67, methanol and acid solution is 0.5 g: 180-200 mL: 370-400 mL.

5. The preparation method according to claim 4, characterized in that: Step 3) The mixing temperature is 20-30° C., the mixing time is 0.5-3 h, and stirring is performed during the mixing process at a stirring speed of 500-700 r / min.

6. The preparation method according to claim 4 or 5, characterized in that: Step 4) The mass volume ratio of ZIF-67K and water is 100 mg: 10-20 mL, and the mass molar ratio of ZIF-67K and bismuth nitrate is 100 mg: 1.5-3 mmol.

7. The preparation method according to claim 6, characterized in that: Step 4) The reaction temperature is 20-30°C, the reaction time is 2-4h, and stirring is performed during the reaction at a speed of 450-650r / min.

8. The preparation method according to claim 7, characterized in that: Step 5) the calcination is carried out under an argon atmosphere, and the calcination includes a primary calcination and a secondary calcination; The primary calcination temperature is 250-350°C, the primary calcination time is 10-30 min, and the heating rate to the primary calcination temperature is 4-6°C / min; The temperature of the secondary calcination is 750-850° C., the time of the secondary calcination is 1-3 hours, and the heating rate to the secondary calcination temperature is 4-6° C. / min.

9. The Bi-based composite catalyst based on ZIF-67 prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the Bi-based composite catalyst based on ZIF-67 as claimed in claim 9 in the electrocatalytic reduction of CO2 to produce formic acid.

Citation Information

Cited By

  • Preparation method and application of topological insulator composite catalytic material

    CN120878860A